Erg25 Controls Host-Cholesterol Uptake Mediated by Aus1p-Associated Sterol-Rich Membrane Domains in Candida glabrata - Okamoto, Michiyo; Takahashi-Nakaguchi, Azusa; Tejima, Kengo; Sasamoto, Kaname; Yamaguchi, Masashi; Aoyama, Toshihiro; Nagi, Minoru; Tanabe, Kohichi; Miyazaki, Yoshitsugu; Nakayama, Hironobu; Sasakawa, Chihiro; Kajiwara, Susumu; et al. (Frontiers in Cell and Developmental Biology, 2022)
The uptake of cholesterol from the host is closely linked to the proliferation of pathogenic fungi and protozoa during infection. For some pathogenic fungi, cholesterol uptake is an important strategy for decreasing susceptibility to antifungals that inhibit ergosterol biosynthesis. In this study, we show that Candida glabrata ERG25, which encodes an enzyme that demethylates 4,4-dimethylzymosterol, is required for cholesterol uptake from host serum. Based on the screening of C. glabrata conditional knockdown mutants for each gene involved in ergosterol biosynthesis, ERG25 knockdown was found to decrease lethality of infected mice. ERG25 knockdown impairs the plasma membrane localization of the sterol importer Aus1p, suggesting that the accumulated 4,4-dimethylzymosterol destabilizes the lipid domain with which Aus1p functionally associates. ERG25 knockdown further influences the structure of the membrane compartment of Can1p (MCC)/eisosomes (ergosterol-rich lipid domains), but not the localization of the membrane proteins Pma1p and Hxt1p, which localize to sterol-poor domains. In the sterol-rich lipid domain, Aus1p-contining domain was mostly independent of MCC/eisosomes, and the nature of these domains was also different: Ausp1-contining domain was a dynamic network-like domain, whereas the MCC/eisosomes was a static dot-like domain. However, deletion of MCC/eisosomes was observed to influence the localization of Aus1p after Aus1p was transported from the endoplasmic reticulum (ER) through the Golgi apparatus to the plasma membrane. These findings suggest that ERG25 plays a key role in stabilizing sterol-rich lipid domains, constituting a promising candidate target for antifungal therapy.